Նավթը և Իրանի հարաբերությունները Պարսից ծոցի երկրների հետ 1960-1970 թթ. - Խաչատուրյան, Ալբերտ (Ասողիկ հրատ.)
It has been suggested that Iran's relations with the Gulf oil-prodicing Arab states have had cooperative and competitive dimensions. While enjoying similar interests in maintaining the high price of oil, the improvement of concessions, and maintenance of the flow of oil, interests have diverged and the competitive dimension has intruded on the rate of production of individual countries. Throughout the decade the Iran government has souglit to regain its position as the Gulfs leading oil producer and has adopted a hard Iine attitude toward both the oil companies and the other producing states in pursuit of this goal.
Keywords: Պատմություն; Քաղաքականություն